A Study of Social and Psychological Empowerment of Sakshar Mahila Samooh Scheme: Unveiling the Challenges and Potential Solutions for Women Empowerment in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A lot may be learned about women in Indian society by looking at the country's social indices.As a result of the gender power disparity, relationships based on mutual respect are unrealistic.Institutionalized traditions such as rituals and sacraments in Indian culture serve to unknowingly transmitpatriarchy from one generation to the next. Some of India's most educated and financially secure womenstill fast every day in the hopes of extending their husbands' lives. This shows that women in India arestill the ones to take the hit for sexism and patriarchy. The studies done on the status of women in Indiashow that they face many disadvantages compared to men. Here, we will discuss some of the mostimportant indicators utilizing the current body of empirical research. The advancement of women can bemeasured in a variety of ways. There is a lot of weight placed on the sex ratio. The percentage ofnewborns that are female is known as the female birthrate. The Indian census is more than just apopulation count it also reveals interesting information on the lives of women in India. The Indianculture has taken a step back in time because of its fixation on having sons. In the sake of custom,having a child who is not a male lowers a woman's social position and often causes her psychologicalpain. The discriminatory Putravati Bhawa blessing is still often used in the vast majority of Hinducommunities. Fetal girls are being killed off by highly educated professionals who are using diagnosticequipment meant to spot issues early on in the process. Populations from rural areas are migrating tourban centers in pursuit of abortion clinics that specialize in terminating the lives of female fetuses. If agirl is born into the family, she will be abandoned and, if she survives, likely poisoned. Efforts to solvesocial and cultural issues must involve educating the public, rallying support, and taking collectiveaction.